Beyond empathy: clinical intimacy in nursing practice - Kirk, Timothy W. (Nursing philosophy, 2007)
Understanding, shared meaning, and mutual trust lie at the heart of the therapeutic nurse-patient relationship. This article introduces the concept of clinical intimacy by applying the interpersonal process model of intimacy to the nurse-patient relationship. The distinction between complementary and reciprocal behaviours, and between intimate interactions and intimate relationships, addresses background concerns about the appropriateness of intimacy in nursing relationships. The mutual construction of meaning in the interactive process between nurses and patients is seen to lie at the heart of clinical intimacy as a hermeneutic enterprise. Intimacy is distinguished from empathy based on intentionality and the status and location of meaning. Reasons for continued investigation into clinical intimacy as an explanatory model for nursing as a hermeneutic practice are presented.